Super special relativity - Wagter, Nicholas Jordan (Frontiers in Computational Neuroscience, 2025)
This paper proposes a new theoretical framework for understanding time perception centered on information processing in the brain. We introduce the concept of “perceptual time” as distinct from inertial clock time and develop a model relating perceptual time experience to the brain’s computational capacity and information processing rate. This framework explains phenomena like time dilation and compression during intense experiences in terms of neural information processing, bridging perceptual time with physical theories of time.